Potential of activated carbon in lime mortar plastering in term of fire resistance and thermal performance. Issue 1 (May 2021) - Rahman, M A A; Yazid, A S; Awang, M; Musa, M K; Mustafa, M S S; Hamidon, N; Hashim, N; Ahmad, F
Abstract: The use of lime mortar plastering for wall construction in residential and light commercial buildings has increased significantly over the world. The unique characteristic of hydrated lime increases the strength of the tensile bond. The more considerable the amount of cement content in cement lime mortar, the low the air content; thus, the bond strength stronger. The performance of plastering under fire exposure is an item of significant importance in securing construction. Activated carbon is one known adsorbent which has a high capacity to adsorb gases and improved fire resistance ability of concrete. The purpose of conducting this study is to identify the optimum proportion of lime mortar plastering containing activated carbon with different percentages which is 0%, 10%, 30% and 50% as cement replacement. Therefore, a fire resistance test was conducted on cement plaster mixtures with variable ratio content of activated carbon to identify the optimum proportion according to the temperature reading by an infrared thermometer for 30 minutes. Based on the results obtained, the sample with 30% activated carbon as cement substitution was the most effective since it gave a relatively low initial temperature reading which was 28.2°C. The test showed only a slight increase in temperature after the first five minutes, which is 93.1% and reached 108.2°C at maximum even after 30 minutes of testing. There was no hair crack developed, and no visible of smoke observed from the sample compared to existing plaster which formed hair crack and visible of smoke at 280°C after 16 minutes of testing. Therefore, 30% of activated carbon is the optimum proportion in lime mortar plastering due to ability to resist fire and prevention from hair crack and visible smoke formation. This proportion can be applied to the interior and exterior wall of the building, especially at the compartment wall and along the escape route.